Kepemimpinan Kepala Sekolah dalam Peningkatan Mutu Pendidikan : Studi Kasus di SMK Nurul Jadid - Sri Indah Rahmawati (Jurnal Penelitian Agama, 2021)
The research is focused on the leadership of principals in improving the service and quality of NJ Vocational High Schools, with research questions directed at: What is the function and principals manner management in upgrading school quality and service in NJ Vocational Schools? What is the reality of quality and educational services currently at NJ Vocational School? To express questions, the method used by researchers is a qualitative method, by focus evidence analysis. To extract information and data from the informant (informant), the researcher used document analysis techniques, observation, and then ended with an interview to confirm the data. The results reveal that; Principal's leadership style in improving service and education quality in SMK Nurul Jadid Paiton Probolinggo is a team or democratic management style. Whereas the leadership function that is applied is in line with the concept of leadership which is widely raised by expert observers. The reality of schools quality in SMK Nurul Jadid Paiton Probolinggo, such as, raw inputs develop rapidly, the instrumental quality of inputs is incomplete but effective, and the environmental quality in the educational institutions is harmony.